Reactualization of Al-Ghazali’s Ethics: Internalizing the Values of Ayyuhal Walad in the Era of Digital Disruption Among Generation Z - Abd Rachman Mildan; Abdul Azis (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
For Generation Z, the boundless digital space often becomes a place devoid of civility, marked by the prevalence of hate speech, a loss of respect for scholarly authority, and an instant-gratification mentality that erodes perseverance. This study aims to reinterpret Imam Al-Ghazali’s ethics as presented in the book Ayyuhal Walad as a means of strengthening the character of Generation Z in the face of the moral crisis caused by digital disruption.  This research uses a qualitative method with a library research approach. The library research used to collect data, analyze, and draw conclusions regarding the reinterpretation of the value of adab in the book Ayyuhal Walad from Imam Al-Ghazali’s, based on journals and previous studies. The research findings indicate that the internalization of values in Imam Al-Ghazali’s Ayyuhal Walad among Generation Z in the era of digital disruption encompasses five key findings: the characteristics of Generation Z in the era of digital disruption; psychosocial profiles and mental health vulnerabilities; the identification of digital pathologies; the mapping of values and resolutions; and a model of internalization mechanisms. At its culmination, the success of the reactivation of Ayyuhal Walad culminates in the restoration of the essential function of the intellect of Generation Z; freeing them from the subjugation of artificial algorithms, and guiding them back to fully submit under the completeness of Sharia and Haqiqat, so that they are ready to face the future as digital subjects with integrity, noble manners, and high spiritual awareness.